2020
DOI: 10.7124/bc.000a1e
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines profile in knee cartilage of rats during monoiodoacetate-induced osteoarthritis and administration of probiotic

Abstract: To identify the effect of probiotic (PB) on cytokines profile in knee cartilage of rats with experimental osteoarthritis (OA). Methods. The animals of 1 st (Сontrol) and 3 rd (PB) groups got 50 µL of saline to both hind knees. The animals of 2 nd (MIA-OA) and 4 th groups (MIA-OA-PB) got single injection of 1 mg monoiodoacetate (MIA) dissolved in 50 µL of saline to knee, after which MIA-OA developed for 28 days. PB feeding [was] provided daily for 14 days during the MIA-OA progress. The levels of cytokines (IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 66 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…Intra-articular MIA injection can increase ROS levels that cause chondrocyte death and trigger cartilage deformation, and elevate articular IL-1β, IL-6, COX2 46 , TNF-α, and NF-κB levels 23 , while reducing TGF-β levels in rats 8 . We found that undenatured collagen supplementation decreased most inflammatory cytokine activity, cartilage degradation markers (including MMP3 and COMP), and joint swelling used for joint inflammation monitoring in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-articular MIA injection can increase ROS levels that cause chondrocyte death and trigger cartilage deformation, and elevate articular IL-1β, IL-6, COX2 46 , TNF-α, and NF-κB levels 23 , while reducing TGF-β levels in rats 8 . We found that undenatured collagen supplementation decreased most inflammatory cytokine activity, cartilage degradation markers (including MMP3 and COMP), and joint swelling used for joint inflammation monitoring in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1 plays a central role in immune disorders by activating intracellular T-cell interactions. IL-1β and TNFα are essential triggers of OA development, whereas IL-4, transforming growth factor β (TGF-β), and interferon-gamma (IFNγ) are categorized as anti-inflammatory cytokines in OA 8 . The increase in inflammatory cytokines and reactive oxygen species (ROS) with aging also stimulate matrix metalloproteinases (MMPs) that drive cartilage degradation in OA 9,10 .…”
mentioning
confidence: 99%
“…Probiotic (PB) groups were administered an oral solution of "Multiprobiotic Simbiter®" (Company "О.D.Prolisok", Ukraine) -a biomass of living cells from the symbiosis of 17 strains of microorganisms physiological for mammalian intestines belonging to 11 species. Most strains were taken from All- The choice of this probiotic is due to its effective multicomponent live bacteria composition and previously shown by us anti-inflammatory and antioxidant properties for this pathology [10,11].…”
Section: Materials and Methods Animals And Treatmentsmentioning
confidence: 99%
“…However, the pathophysiology of OA remains unclear. OA was recognized as systemic and local low inflammatory states [3]. Moreover, the metabolic changes such as intestinal microbiota changes also are associated with the pathogenesis of OA [4].…”
Section: Introductionmentioning
confidence: 99%